Subchronic olanzapine exposure leads to increased expression of myelination-related genes in rat fronto-medial cortex. Issue 11 (November 2017) - Ersland, Kari; Skrede, Silje; Stansberg, Christine; Steen, Vidar
Abstract Schizophrenia is a psychotic disorder with severe and disabling symptoms, such as hallucinations, delusions, blunted affect and social withdrawal. The neuropathology remains elusive, but disturbances in immunity-related processes, neuronal connectivity and myelination have consistently been linked to schizophrenia. Antipsychotic drugs can be efficient in reducing symptoms, acting primarily on the dopamine system, but additional biological targets are likely to exist. Here we have screened for novel mechanisms of action in an animal model, using adult rats exposed to long-acting olanzapine, achieving stable and clinically relevant antipsychotic drug concentrations. By microarray-based examination of global gene expression in the fronto-medial cortex, at the single gene- and gene-set level, we observed downregulation of two neuropeptide-encoding genes, Vgf and Cort (fold change −1, 25 and −1, 48, respectively) in response to olanzapine exposure. Furthermore, we demonstrated significant upregulation of five out of ~2000 GO predefined gene sets after olanzapine exposure. Strikingly, all were linked to myelination and oligodendrocyte development; "Ensheathment of neurons", "Axon ensheathment", "Myelination", "Myelin sheath" and "Oligodendrocyte development" (FDR-values < 25). Sixteen of the leading edge genes in these gene sets were analysed independently by qPCR, of which 11 genes displayed significant upregulation, includingPlp1, Mal, Mag andCnp (fold change: 1, 30, 1, 50, 1, 30 and 1, 15, respectively). Several of the upregulated genes (e.g.MAG, MAL andCNP ) have previously been reported as downregulated in post-mortem brain samples from schizophrenia patients. Although caution needs to be taken when extrapolating results from animal studies to humans, the data suggest a role for olanzapine in alleviating myelination-related dysfunction in schizophrenia.